Therapeutic targeting of the PLK1-PRC1-axis triggers cell death in genomically silent childhood cancer - Li, Jing; Ohmura, Shunya; Marchetto, Aruna; Orth, Martin F.; Imle, Roland; Dallmayer, Marlene; Musa, Julian; Knott, Maximilian M. L.; Hölting, Tilman; Stein, Stefanie; Funk, Cornelius M.; Sastre, Ana; et al. (Nature Communications, 2021)
Chromosomal instability (CIN) is a hallmark of cancer1. Yet, many childhood cancers, such as Ewing sarcoma (EwS), feature remarkably ‘silent’ genomes with minimal CIN2. Here, we show in the EwS model how uncoupling of mitosis and cytokinesis via targeting protein regulator of cytokinesis 1 (PRC1) or its activating polo-like kinase 1 (PLK1) can be employed to induce fatal genomic instability and tumor regression. We find that the EwS-specific oncogenic transcription factor EWSR1-FLI1 hijacks PRC1, which physiologically safeguards controlled cell division, through binding to a proximal enhancer-like GGAA-microsatellite, thereby promoting tumor growth and poor clinical outcome. Via integration of transcriptome-profiling and functional in vitro and in vivo experiments including CRISPR-mediated enhancer editing, we discover that high PRC1 expression creates a therapeutic vulnerability toward PLK1 inhibition that can repress even chemo-resistant EwS cells by triggering mitotic catastrophe.